Emergence and Infestation Level of Hypothenemus hampei (Coleoptera: Curculionidae) on Coffee Berries on the Plant or on the Ground During the Post-harvest Period in Brazil. Issue 2 (3rd April 2021) - Pereira, Adriano E; Gontijo, Pablo C; Fantine, Andreza K; Tinoco, Ricardo S; Ellersieck, Mark R; Carvalho, Geraldo A; Zanuncio, José C; Vilela, Evaldo F
Abstract: The coffee berry borer (CBB), Hypothenemus hampei Ferrari (Coleoptera: Curculionidae), is the most important coffee pest in most of the coffee growing countries. CBB females leave old dry berries after harvest and search for dry noninfested berries on the plant or on the ground to lay eggs or to use as refuge until new berries are available on the coffee trees in the following season. The CBB infestation level and emergence from berries on the ground or on the plants were evaluated in two fields post-harvest in the Spring in Brazil over two seasons. Twenty infested or noninfested berries in separate cages (250 ml plastic cups) were placed on the plants or on the ground under the tree canopy, in each field. The number of infested berries and CBB females that emerged from the infested berries were recorded weekly. CBB emergence was higher from berries on the ground than those on the coffee trees in both seasons, whereas CBB infestation was higher on coffee berries on the plants than those on the ground in season I. Insolation (hours of sunlight) and temperature were the main covariates that affected emergence and infestation by this insect. The results are discussed for monitoring CBB during the time of dispersal with implications on integrated management of this pest.